(untitled) (Perner’s Contacts, 2011)
In this paper we describe brute force methods of cross ambiguity function (CAF) which is key function for successful location tracking for passive radar systems. The CAF depends upon the direct and the reflected signals from targets. The CAF represents the power spectral density function of the cross correlation between direct and reflected signals from the target. The computation of CAF in real-time is a challenging task for parallel programming techniques.